Evaluation of the Baan Mankong Housing Project on Government Surplus Land - Thanindechanan, Nantawat; Sawatphon, Chavalit (Journal of Law and Political Affairs, 2025)
This article aims to study the current situation and evaluate the Baan Mankong Housing Project for low-income households on government surplus land. The study employed in-depth interviews and focus group discussions with project participants across 17 projects in five regions. The findings revealed that nine projects successfully completed housing construction as planned, six projects were still in progress, and two projects could not proceed due to the unavailability of government land or the residents’ reluctance to take out housing loans. In these cases, the residents already had homes on the government land and only sought to formalize tenancy under the law. Some participants faced difficulties in repaying loans on a monthly basis due to a lack of stable income. Applying the CIPP Model, the Context dimension reflects structural urban inequality, which forces people to reside in informal settlements without secure housing. The Input dimension highlights the mobilization of resources from both the state and community, as well as the community-based management mechanisms. The Process dimension emphasizes the participatory implementation approach, despite challenges in legal understanding and interpretation. The Product dimension demonstrates diverse outcomes, including successful housing construction, land tenure security, improved quality of life, and continuing challenges in loan repayment for some members.